Impact of crop establishment methods and nitrogen levels on quality, nutrient uptake, productivity and profitability of wheat (Triticum aestivum L.) - Gupta, Gaurendra; Hooda, V.S.; Thakral, S.K.; Kumar, Navish; Kumar, Vikram; Kumar, Amit; Dwivedi, Ashish (Annals of Agricultural Research, 2018)
A field experiment was conducted to assess the effect of five crop establishment methods and fournitrogen levels on performance, factor productively and profitability of wheat during rabi season of2013-14 at Chaudhary Charan Singh Haryana Agricultural University (CCSHAU), Hisar, Haryanausing split plot design with three replications. Remarkable effects were noted under drill sowing at18 and 20 cm and bed planting with three rows found better in terms of growth, yield and totalnutrient uptake by wheat as compared to 16 cm row spacing and two rows bed planting. Totalnutrient uptake was significantly higher when sowing was done with drill at 18 cm row spacing.The highest grain yield (5.09 t ha–1), net returns and B: C was obtained with 18 cm row spacing thanother crop establishment methods. The successive application of N from 100%, 112.5% and 125%recommended dose of nitrogen (RDN), significantly enhanced various growth and yield parametersincluding fertile tillers resulting in higher grain and straw yields of wheat. The highest grain yield(5.17 t ha–1) obtained with application of 125% RDN which was at par with yield under 112.5%RDN.